A Self-Sustained Microcontroller Regulated Energy Extraction Network for Piezoelectric Energy Harvesters - Dorsch, Philipp; Götz, Stefan; Hubert, Florian; Rupitsch, Stefan (SMSI 2020 - Sensors and Instrumentation, 2020)
The presented energy extraction network regulates the output voltage of a rectifier in order to meet the point of maximum power extraction. This point depends on the mechanical excitation of a piezoelectric energy harvester. The obtained results are compared to an unregulated approach. Though the pro- posed solution requires a higher supply current, the overall power output remained comparable. Addi- tionally, the option of managing the harvested energy was gained. This leads to a promissing feature for various self-sustained applications.
Keywords: Piezoelectricity; Internet of Things; Asset-Tracking; Energy-Autarchic; Low-Power and Harvesting